Impact of post-torrefaction process on biochar formation from wood pellets and self-heating phenomena for production safety. (15th September 2020) - Arriola, Emmanuel; Chen, Wei-Hsin; Chih, Yi-Kai; De Luna, Mark Daniel; Show, Pau Loke
Abstract: The advancement of torrefaction in the industry raises safety issues lately. This work aims to investigate the impact of post-torrefaction upon biochar formation and the self-heating phenomena of torrefied wood pellets. Three operating scenarios are taken into account. Specifically, dried wood pellets are first torrefied in nitrogen at various temperatures (200–300 °C) followed by immediate exposure to N2 or air with/without keeping temperature, namely, the post-torrefaction, to examine the self-heating behavior. Meanwhile, the influences of torrefaction temperature, duration, and self-heating on biochar's characteristics are analyzed. It is found that self-heating with the highest temperature rise of 61 °C is triggered when the biochars are in an oxidative post-torrefaction process with keeping temperature. Alternatively, oxidative post-torrefaction without keeping temperature can efficiently intensify the pellets' calorific value up to 42%. The X-ray photoelectron spectroscopy analysis reveals the depletion of the CO functional group. It is concluded that uncontrolled self-heating in large scale production will lead to combustion and make biochar unsafe. Alternatively, if heat accumulation inside the biochar piles can be prevented, the oxidative environment that causes self-heating can open a lot of research opportunities that can help in the advancement of torrefaction technologies for biomass as an alternative source of energy. Graphical abstract: Image 1 Highlights: Self-heating phenomena are investigated using three different scenarios. Three scenarios under different post-torrefaction processes are taken into account. Self-heating occurs when oxidative post-torrefaction with keeping temperature is operated. Oxidative post-torrefaction without keeping temperature intensifies fuel's calorific value. XPS analysis reveals the depletion of the CO functional group in biomass after torrefaction.